Status of heavy metal in sediments of the Turag river in Bangladesh (Progressive Agriculture, 2016)
The experiment was conducted to appraise the level of Cr, Pb, Cd, Ni, Zn, Cu, Fe and Mn contamination in 15 sediment samples of upstream of Turag river, at the Department of Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh. The concentrations of Cr, Pb, Cd, Ni, Zn, Cu, Fe and Mn were 178.0, 18.3, 0.8, 155.4, 194.1, 54.8, 13679 and 5501.6 µg g-1 and the pH and EC ranged from 2.01-7.85 and 391-3910µS cm-1, respectively. Heavy metal concentrations were compared with geochemical background and standard values of previous report on the Turag and other rivers in Bangladesh. The average concentrations of Cr, Zn and Ni in sediments of the Turag are almost twice of the geochemical background i.e. average worldwide shale standard and continental upper crust. Cadmium is about three times higher than the geochemical background values.  Chromium and Ni concentration exceeded the severe effect level (SEL), where as Cd, Zn and Cu exceeded toxicity reference values (TRV). The average Enrichment Factors (EFc) for Mn, Cd, Cr and Ni reflected moderate to extremely contaminated pollution. The pollution load index (PLI) varied from 1.65 to 3.21. The geoaccumulation index (Igeo) for Mn of 11 locations and Cd for a single location were greater than 2.0, and exhibited moderately to strongly polluted sediment quality. The Igeo for Zn in two locations and Ni in one location were greater than 1.0, indicated moderately polluted sediment quality. Sediment pollution load signaled alarming condition for city dwellers and aquatic ecosystem of the Turag river. Pollution sources to be sealed immediately and continuous monitoring on pollution prevention and cleanup operation is suggested.Progressive Agriculture 27 (2): 78-85, 2016